2018
DOI: 10.17826/cumj.336142
|View full text |Cite
|
Sign up to set email alerts
|

Bir kutanöz leishmaniasis endemik bölgesi olan Adana’nın Karaisalı ilçesinde kum sineği faunası ve çevresel parametrelerin belirlenmesi

Abstract: Öz Purpose: This paper presents the results of an entomological survey in an endemic focus of cutaneous leishmaniasis in Karaisali province of Adana in Turkey. Materials and Methods: There were two field works in two consecutive years (2013 and 2014), which 1088 sand fly specimens were captured using 136 light traps which were conducted in 11 villages of Karaisali located in southwest part of Adana. Results: Totally, six Phlebotomus species were described: Phlebotomus tobbi (41.54%), Phlebotomus neglectus/syri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…The results indicate that the total annual precipitation (mm) and the percentage of the area with Amazonian humid forest were associated with cases of leishmaniasis, confirming that the impact of climatic factors on ecological conditions contributes to the multiplication of the leishmaniasis vector disease [15][16][17]. Similarly, in a study carried out in Argentina, the results presented on the eco-epidemiology of leishmaniasis showed that climatic changes result in changes in the probability of effective vector-human reservoir contacts [27].…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The results indicate that the total annual precipitation (mm) and the percentage of the area with Amazonian humid forest were associated with cases of leishmaniasis, confirming that the impact of climatic factors on ecological conditions contributes to the multiplication of the leishmaniasis vector disease [15][16][17]. Similarly, in a study carried out in Argentina, the results presented on the eco-epidemiology of leishmaniasis showed that climatic changes result in changes in the probability of effective vector-human reservoir contacts [27].…”
Section: Discussionmentioning
confidence: 57%
“…It has been found that the ranges of temperature and relative humidity for the development of sandflies are between 21-29 • C and 80-90%, respectively [16]. Also, within environmental factors, it has been reported that vegetation and altitude play especially important roles in determining the habitats and vectorial capacities of sandflies [17].…”
Section: Introductionmentioning
confidence: 99%